Deletion of Cryab increases the vulnerability of mice to the addiction-like effects of the cannabinoid JWH-018 via upregulation of striatal NF-κB expression - Sayson, Leandro Val; Ortiz, Darlene Mae; Lee, Hyun Jun; Kim, Mikyung; Custodio, Raly James Perez; Yun, Jaesuk; Lee, Chae Hyeon; Lee, Yong Sup; Cha, Hye Jin; Cheong, Jae Hoon; Kim, Hee Jin (Frontiers in Pharmacology, 2023)
Synthetic cannabinoids have exhibited unpredictable abuse liabilities, especially self-administration (SA) responses in normal rodent models, despite seemingly inducing addiction-like effects in humans. Thus, an efficient pre-clinical model must be developed to determine cannabinoid abuse potential in animals and describe the mechanism that may mediate cannabinoid sensitivity. The Cryab knockout (KO) mice were recently discovered to be potentially sensitive to the addictive effects of psychoactive drugs. Herein, we examined the responses of Cryab KO mice to JWH-018 using SA, conditioned place preference, and electroencephalography. Additionally, the effects of repeated JWH-018 exposure on endocannabinoid- and dopamine-related genes in various addiction-associated brain regions were examined, along with protein expressions involving neuroinflammation and synaptic plasticity. Cryab KO mice exhibited greater cannabinoid-induced SA responses and place preference, along with divergent gamma wave alterations, compared to wild-type (WT) mice, implying their higher sensitivity to cannabinoids. Endocannabinoid- or dopamine-related mRNA expressions and accumbal dopamine concentrations after repeated JWH-018 exposure were not significantly different between the WT and Cryab KO mice. Further analyses revealed that repeated JWH-018 administration led to possibly greater neuroinflammation in Cryab KO mice, which may arise from upregulated NF-κB, accompanied by higher expressions of synaptic plasticity markers, which might have contributed to the development of cannabinoid addiction-related behavior in Cryab KO mice. These findings signify that increased neuroinflammation via NF-κB may mediate the enhanced addiction-like responses of Cryab KO mice to cannabinoids. Altogether, Cryab KO mice may be a potential model for cannabinoid abuse susceptibility.